Kinematic Analysis of the Drag Push Technique on Ball Speed in Indoor Hockey - S Salman; Tono Haryono (Universitas Pendidikan Indonesia, 2023)
This research was aimed to analyze the drag push technique using a 3D kinematic analysis approach. Biomechanical parameters have a significant effect on the drag push technique so that they can be specific recommendations for training the drag push technique. The method used in this research was quantitative descriptive method. The samples participating in this study were professional hockey players from the Indonesian National men's team (n: 12; age: 21.3 ± 2.5 years; weight: 71.7 ± 5.2 kg; height: 170 ± 2, 4 cm; BMI: 21.2 ± 1.7; competition experience: 4 ± 2.2 years). The instrument used in this research was a High-Speed Camera (Fastecimaging; San Diego, USA) with a shutter speed of 120Hz to record the athlete movements when performing the drag push technique. Radar Speed Gun (Bushnell; Kansas, USA) was used to detect ball speed resulting from the drag push technique. Motion Analysis Software (Frame-DIAS; Fukuoka, Japan) was used to analyze motion kinematics in three dimensions. The collected data were analyzed statistically using descriptive statistics and stepwise linear regression. The results revealed that drag distance and stance width were the dominant variables for optimizing push-in performance of Indonesian Indoor Hockey athletes. This study suggests that maximizing the distance of the foot to the ball at the start of the push-in is important to maximize the distance of the pull and using a combination of simultaneous and sequential segment rotations is beneficial to optimize the ball speed and the drag speed.